2016
DOI: 10.1016/j.bbr.2015.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in behavior and neural development and their role in adolescent vulnerability to substance use

Abstract: Adolescents are especially prone to risky behavior and to the emergence of psychological disorders like substance abuse, anxiety and depression. However, there is a sex (or gender) difference in this vulnerability, with females being more prone to developing internalizing disorders and males being more likely to engage in risky behavior and drug use. While several researchers have proposed that there is a relationship between corticolimbic circuit development and adolescent vulnerability, the current proposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 128 publications
(239 reference statements)
3
55
2
1
Order By: Relevance
“…We have previously hypothesized that drinking is more strongly related to impulsivity in males (Hammerslag & Gulley 2016), while anxiety may be a better predictor of drinking for females (Varlinskaya et al 2015;Hammerslag & Gulley 2016). In this study the relationship between impulsive action and drinking was significant only in males, however there was a trend toward the same relationship in females and thus the importance of this sex difference is unclear.…”
Section: Discussioncontrasting
confidence: 53%
“…We have previously hypothesized that drinking is more strongly related to impulsivity in males (Hammerslag & Gulley 2016), while anxiety may be a better predictor of drinking for females (Varlinskaya et al 2015;Hammerslag & Gulley 2016). In this study the relationship between impulsive action and drinking was significant only in males, however there was a trend toward the same relationship in females and thus the importance of this sex difference is unclear.…”
Section: Discussioncontrasting
confidence: 53%
“…Thus, the ability of drugs of abuse to alter the normal developmental trajectory of prefrontal circuitry may be a principal mechanism through which adolescent drug exposure can lead to longstanding, if not permanent, changes in prefrontal control over behavior. It will be important for future studies to determine the precise mechanisms that underlie drug-induced plasticity leading to vulnerability, as well as understand what factors might lead to resilience to the effects of drugs (Hammerslag and Gulley, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the continuous maturation of dopamine function in the mPFC throughout late-adolescence to adulthood coincides with improvement or emergence of complex cognitive behavior (Naneix et al, 2012). Thus, disruption of such delayed development by drug exposure during adolescence may induce specific neural and behavioral adaptations that contribute to a heightened vulnerability to addiction and comorbid mental disorders (Gulley and Juraska, 2013; Hammerslag and Gulley, 2016). An early study (Brandon et al, 2001) showing that exposure to methylphenidate during adolescence led to cross-sensitization to cocaine and increased cocaine self-administration in adulthood is consistent with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence suggests that illicit substance use during adolescence may profoundly alter brain development (Gulley and Juraska, 2013; Spear, 2015) and potentially increase the risk of future substance abuse and addiction (Paus et al, 2008; Hammerslag and Gulley, 2016). Amphetamine (AMPH) is among the most widely abused drugs and it has been estimated that about 10.3% of the US population has used AMPH at least once by the 10 th grade (UNODC, 2010).…”
Section: Introductionmentioning
confidence: 99%